1996
DOI: 10.1209/epl/i1996-00222-0
|View full text |Cite
|
Sign up to set email alerts
|

Inelastic neutron and Raman scattering of poly(methyl methacrylate): Nanostructure of polymer glasses

Abstract: Low-energy excitations were investigated in amorphous poly(methyl methacrylate) by means of both neutron and Raman scatterings, in a wide temperature interval. The frequency dependence of the light-vibration coupling coefficient was deduced, especially at low temperature where the quasi-elastic contribution is not significant; it was not found to be linear. The vibrational density-of-states anomaly is interpreted in the frame of a non-continuous glassy nanostructure, which is characterized by a log-normal size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
49
0
5

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 27 publications
7
49
0
5
Order By: Relevance
“…The boson peak appears at an energy slightly lower than 2 meV for pure PMMA-H, as observed before [3], and higher for pure DBP (Figure 1). The relative intensity at low energy is higher for pure PMMA than for pure DBP, and decreases with plasticization.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…The boson peak appears at an energy slightly lower than 2 meV for pure PMMA-H, as observed before [3], and higher for pure DBP (Figure 1). The relative intensity at low energy is higher for pure PMMA than for pure DBP, and decreases with plasticization.…”
Section: Resultssupporting
confidence: 80%
“…Furthermore such arrangement is quasiperiodic with a period close to 4 nm. This inhomogeneity of the plasticized polymer was assumed to be due to the cohesion inhomogeneity of the glassy polymer without plasticizer: "More cohesive are separated by softer interdomain zones" [2,3]. The other interesting experimental result is the increase of the excess of low-frequency Raman scattering (LFRS) or Raman boson peak by plasticization: the boson peak is more intense than the one obtained by adding the LFRS of the two components (PMMA and DBP) according to the composition of the plasticized material.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, computer simulation of large fractal networks by Yakubo et al [66] showed that there are no excess excitations in the crossover region. It is often assumed that the origin of the boson peak is a confined phonon [46,47,67]. For amorphous polymers it was assumed that a glassy state has a non-continuous structure due to a stronger bonding between atoms in blobs than between atoms in different nearest-neighbor blobs.…”
Section: Some Modelsmentioning
confidence: 99%
“…Though some attempts in this direction were made in the past [22], a definite conclusion as to the shape of C(ω) has not been reached [8,17,23], mainly due to the presence of "spurious" effects in RS (namely, the presence of quasi-elastic scattering (QES)…”
Section: Spectral Information On the Bp Is Usually Obtained By Inelasmentioning
confidence: 99%